Social associations and habitat selection delineate two subpopulations of west coast transient killer whales (Orcinus orca rectipinnus) in the California Current System - Josh D. McInnes; Andrew W. Trites; Kevin M. Lester; Chelsea R. Mathieson; Lawrence M. Dill; Jeffrey E. Moore; Marilyn E. Dahlheim; Jonathan J. Scordino; K. S. Jasper Kanes; Paula A. Olson (PLoS ONE, 2025)
West coast transient (mammal-eating) killer whales ( Orcinus orca rectipinnus ) inhabit the California Current off the west coast of North America from southern British Columbia, Canada to southern California, United States. Although genetically distinct from other killer whale populations, observed differences in social associations and habitat use of some individuals suggest that west coast transient killer whales may not constitute a single, socially and spatially discrete population. We analyzed 2,232 georeferenced encounters of photographed transient killer whales collected between 2005 and 2021 from dedicated research ship surveys, small vessel surveys, and opportunistic sightings, to assess their social and population structure in relation to habitat characteristics. Using social network and geospatial analysis software, we identified two socially and geographically independent subpopulations with cohesive social structures—one that frequents shallow nearshore coastal areas (inner coast subpopulation) and a second that primarily inhabits deeper waters along the continental shelf-break and slope (outer coast subpopulation). The inner coast subpopulation (n = 345 photo-identified whales) most commonly occurred in intracoastal waterways and along the shallow coastal margins of the continental shelf where they fed primarily on pinnipeds and small cetaceans within 5 km of shore. In contrast, the outer coast subpopulation (n = 211 photo-identified whales) occurred within 6.1 km of the continental shelf-break and in far offshore waters (e.g., 120 km offshore) near deep submarine canyons and subsurface sea mounts—where they fed primarily on pelagic pinnipeds, oceanic delphinids, and large cetaceans. Our findings demonstrate that the west coast transient killer whale population, though genetically distinct, is structured into two socially and ecologically distinct subpopulations along the west coast of North America. This division underscores the need for conservation efforts to be tailored to their unique ecological and social characteristics.